Immune Functions of Erythrocytes in Osteichthyes - Stosik, Michał; Tokarz-Deptuła, Beata; Deptuła, Jakub; Deptuła, Wiesław (Frontiers in Immunology, 2020)
Red blood cells (RBCs) -erythrocytes of Osteichthyes are primarily known for their involvement in the process of gas exchange and respiration. Currently, physiological properties of RCBs in fish should also include their ability to participate in defence processes as part of the innate and adaptive immune mechanisms. In response to viruses, bacteria and fungi or recombinant nanoparticles, they can modulate expression of genes responsible for immune reactions, influence activity of leukocytes and produce cytokines, antimicrobial peptides and paracrine intercellular signalling molecules. Via the complement system (CR1 receptor) and due to their phagocytic properties (erythrophagocytosis), RBCs of Osteichthyes can eliminate pathogens. In addition, they are probably involved in the immune response as antigen-presenting cells via major histocompatibility complex class II (MHC II) antigens.